FEATURES OF HAEMODINAMIC PARAMETRES OF PATIENTS WITH CHOLELITHYASIS BY ILLNESS AT SIMULTANEOUS OPERATIONS - Аль Ширафі Мохаммед Авад (World of Medicine and Biology, 2010)
In 42 patients cholecystectomi is executed by the opened access and in 299 – executed a laparoscopic method. Probed the indexes of hemodynamics in the day of operation, on 1 – 3 and 5 days after operative interference. It is set that laparoscopic method and traditional single-plane operations at patients from accompanied cholelithyasis illness by disorders of hemodynamics. A laparoscopic method has considerable advantages in a after operation period, namely: a pulse, systole, diastole and middle arteriotony, and also frequency of respiratory motions, during the leadthrough of laparoscopic operative interferences settled into a shape on the third days. While at traditional access to the organs of abdominal region these parameters were normalized, in swingeing majority on the fifth days of after operation period.